Integrated Approaches for Adsorption and Incorporation Testing of Green-Synthesized TiO2NPs Mediated by Seed-Priming Technology in Punica granatum L. - Hala M. Abdelmigid; Amal Ahmed Alyamani; Nahed Ahmed Hussien; Maissa M. Morsi; Afnan Alhumaidi (Agronomy, 2022)
Seed priming is a novel approach that is undertaken to improve seed germination and therefore potentially enhance growth and yield. Low-cost, eco-friendly, and efficient seed treatment as a means of enhancing growth and yield is still being sought for high-value crops such as pomegranates (Punica granatum L.), particularly in areas situated at high altitudes such as the Taif region. The uptake of nanoparticles (NPs) by plants provides a potential pathway for NP exposure. Therefore, it is imperative to understand NP uptake via seed priming and their unique properties within plants. In the present study, titanium dioxide nanoparticles (TiO2NPs) were green-synthesized and utilized as priming agents for pomegranate seeds at a concentration of 40 mg/mL for 24 h. The adsorption of NPs was verified by scanning electron microscopy (SEM) and energy dispersive X-ray analysis/spectroscopy (EDX), while their incorporation was detected by transmission electron microscopy (TEM). To validate the EM results, X-ray fluorescence (XRF) and inductively coupled plasma optical emission spectroscopy (ICP–OES) techniques were further undertaken. The results confirmed the successful synthesis of pure anatase TiO2NPs by employing aqueous extracts of pomegranate fruit peel (PPE) and coffee ground beans (CE). All of the analytical techniques employed in this research confirmed the incorporation of TiO2NPs inside seeds, even after storage during priming treatment. This study lays the foundation for future sustainable seed technologies in terms of crop productivity and seed germination.